2018
DOI: 10.5603/fhc.a2018.0010
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study on neuropilin 1 (NRP1) immunoexpression in oral squamous cell carcinoma

Abstract: The present study revealed overexpression of NRP1 in OSCC, especially in OSCC patients with metasta-sis, suggesting that NRP1 could potentially contribute to metastasis of oral cancer. The correlation between the number of NRP1+ infiltrating cells and CD163+ macrophages suggests that NRP1+ infiltrating macrophages are present in tumor microenvironment and may play a role in the progressions of oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…We have also previously demonstrated that M2 macrophages contribute to the process of angiogenesis in the esophageal squamous cell carcinoma microenvironment [18]. In addition, several researchers have reported that CD163 + macrophages promote angiogenesis in oral squamous cell carcinoma [31][32][33]. On the other hand, to our knowledge, there is a lack of reports on angiogenesis in OVX.…”
Section: Discussionmentioning
confidence: 87%
“…We have also previously demonstrated that M2 macrophages contribute to the process of angiogenesis in the esophageal squamous cell carcinoma microenvironment [18]. In addition, several researchers have reported that CD163 + macrophages promote angiogenesis in oral squamous cell carcinoma [31][32][33]. On the other hand, to our knowledge, there is a lack of reports on angiogenesis in OVX.…”
Section: Discussionmentioning
confidence: 87%
“…Neuropilins were also shown to engage in tumor neovascularization and metastasis, and their co-expression was shown to be correlated with the increased vascularity and poor prognosis for NSCLC patients [ 58 ]. The expression of both NRP1 and NRP2 was found in many tumor types [ 59 ], where their overexpression contributed to metastasis [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropilin-1 (NRP1) is a transmembrane or cytosolic protein that acts on several signaling pathways, such as angiogenesis through VEGF and HGF in endothelial cells [ 48 ], and is a tumor promotor overexpressed in several tumor tissues [ 49 , 50 , 51 ]. Issit et al revealed a physical interaction between NRP1 and ABCB8.…”
Section: Heme Metabolism—a Complex Network Tightly Regulated By Enzym...mentioning
confidence: 99%
“…NRP1 is a tumor promotor overexpressed in several tumor tissues such as oral squamous cell carcinoma [ 49 ], breast [ 50 ] and lung [ 51 ] cancers. Interestingly, only one study was found to connect NRP1 to heme synthesis.…”
Section: Concerning Ppix Selective Accumulation In Neoplastic Cellsmentioning
confidence: 99%